Inovasi Penanggulangan Stunting Melalui Implementasi Program OMASUKA di Kelurahan Gajah Sakti Kecamatan Mandau Kabupaten Bengkalis - Mustiqowati Ummul Fithriyyah; Elza Nabila Jumiasri; Mustafa Mustafa (ARISTO, 2026)
This study aims to determine the implementation of the OMASUKA (Mandau Special Healthy Food Taxi for Toddlers) program by TP-PKK in tackling stunting in Gajah Sakti Village, Mandau District, Bengkalis Regency. This program is one of the community-based service innovations in the form of providing supplementary food delivered directly to the homes of toddlers with stunting status. The background of this study is based on the high rate of stunting in the area and the need for community-based interventions to overcome stunting. This study uses a qualitative descriptive approach with data collection techniques in the form of interviews, observation, documentation and triangulation. The theory used as an analytical tool is the theory of policy implementation according to George Edward III, which includes communication, resources, disposition, and bureaucratic structure. The results of the study indicate that the implementation of the OMASUKA program has been running quite well. However, several inhibiting factors were found, firstly in the communication aspect, although coordination between policy implementers is running well, mothers of toddlers who receive benefits still have minimal understanding of the OMASUKA program and the issue of stunting. Then, the program implementation has not been consistent due to the uncertain frequency of activities. As well as limited operational facilities are inadequate. Keywords: Stunting; Policy Implementation; TP-PKK; OMASUKA Program; Toddler Nutrition;